Perancangan Dan Analisis Jembatan Rangka Baja Canai Dingin (Cold Formed Steel) Untuk Pejalan Kaki - Reza Ermawan; Ismeddiyanto Ismeddiyanto; Ridwan Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Cold-formed steel is one of the alternative material that can be used as for truss bridge structures. The high slenderness of cold-formed steel is very prone to buckling (local, distortion, and global) so that the determination of cross-section capacity will be different from hot rolled steel. In Indonesia, cold-formed steel as a structure has been regulated in SNI 7971:2013. According to SNI 7971:2013, there are two methods to determine cross-sectional capacity of cold-formed steel, effective width and direct strength method. The design of a cold-formed steel truss bridge for the loading of class II pedestrians, with a combination of loading from AASHTO LRFD Guide Specification for the Design of Pedestrian Bridge (2009).This research aimed to study the efficiency of truss bridge configurations by comparing bridge weight-displacement ratio of the analyzed bridge truss systems. Bridges were designed in three truss system configurations, Warren, Pratt and Howe. The tension and compression elements, were designed with effective width and direct strength method which were available in CUFSM4 software. The results of the analysis showed that the addition of bridge weight was proportional to the reduction of bridge deflection. Warren truss bridge system produced the smallest ratio of efficiency among the three system, with a value of 5,11, while the Pratt and Howe truss bridge system had the ratio of efficiency of 5,36 and 5,50, respectively. Furthermore, the reduction of the compressive area was also proportional to the slenderness of the element analyzed with effective width method. The cross sections that had high slenderness, failures occured in local buckling. If the cross-section did not experienced global buckling on the elastic buckling curve, the failure occured in the distortion buckling. The direct strength method also produced a higher compressive capacity of 9.33% in profile variations and 8.84% in length variations compared to the effective width method.Keywords : Truss bridge, cold formed steel, truss system, direct stength method, effective widths method.